John Stuart Mill a very short introduction - Claeys, Gregory 1951- (Very short introductions, 2022)
John Stuart Mill (1806-73) is widely regarded as the leading liberal philosopher, economist, and political theorist of 19th century Britain. This book offers a brief survey of his life and ideas, highlighting the philosophical context for his work, exploring the key themes in his writings, and analysing their lasting influence.